Development and Validation of a New Technique for Ultrasound-Guided Stellate Ganglion Block. Issue 5 (1st August 2009) - Gofeld, Michael; Bhatia, Anuj; Abbas, Sherif; Ganapathy, Sugantha; Johnson, Marjorie
Abstract : Background and Objectives: Although the stellate ganglion is located anteriorly to the first rib, anesthetic block is routinely performed at the C6 level. Ultrasonography allegedly improves accuracy of needle placement and spread of injectate. The technique is relatively new, and the optimal approach has not been determined. Moreover, the location of the cervical sympathetic trunk relative to the prevertebral fascia is debatable. Methods: Three-dimensional sonography was performed on 10 healthy volunteers, and image reconstruction was completed. On the basis of analysis of pertinent anatomy, a lateral trajectory for needle placement was simulated. Accuracy was tested by injection of methylene blue in cadavers. A clinical validation study was then conducted. A block needle was inserted according to the predetermined lateral path, and 5 mL of a mixture of bupivacaine and iohexol was injected. Spread of the contrast agent was verified fluoroscopically. Results: Image reconstruction revealed that the cervical sympathetic trunk is located posterolaterally to the prevertebral fascia on the surface of the longus colli muscle. The mean anteroposterior width of the muscle at the C6 level was 11 mm. The lateral approach does not interfere with any visceral or nerve structures. Anatomic dissection in cadavers confirmed entirely subfascial spread of the dye and staining of the sympathetic trunk. The contrast agent spread was seen in all patients between the C4 and T1 levels in a typical prevertebral pattern. Conclusions: This study revealed that, at the C6 level, the cervical sympathetic trunk lies entirely subfascially. Subfascial injection via the lateral approach ensures reliable spread of a solution to the stellate ganglion.